Xeroderma pigmentosum complementation group E and UV-damaged DNA-binding protein - Tang, Jean (2002)
UV-damaged DNA-binding protein (UV-DDB) is composed of two subunits, DDB1 (p127) and DDB2 (p48). Mutations in the DDB2 gene inactivate UV-DDB in individuals from complementation group E of xeroderma pigmentosum (XP-E), an autosomal recessive disease characterized by sun sensitivity, severe risk for skin cancer and defective nucleotide excision repair. UV-DDB is also deficient in many rodent tissues, exposing a shortcoming in rodent models for cancer. In vitro, UV-DDB binds to cyclobutane pyrimidine dimers (CPDs), 6–4 photoproducts and other DNA lesions, stimulating the excision of CPDs, and to a lesser extent, of 6–4 photoproducts. In vivo, UV-DDB plays an important role in the p53-dependent response of mammalian cells to DNA damage. When cells are exposed to UV, the resulting accumulation of p53 activates DDB2 transcription, which leads to increased levels of UV-DDB. Binding of UV-DDB to CPDs targets these lesions for global genomic repair, suppressing mutations without affecting UV survival. Apparently, cells are able to survive with unrepaired CPDs because of the activity of bypass DNA polymerases. Finally, there is evidence that UV-DDB may have roles in the cell that are distinct from DNA repair.